EFFECT OF HARDNESS OF WATER ON THE ACUTE TOXCITY OF DIMETHOATE TO PUNTIUS TICTO (HAM.) - GANESHWADE, R.M.; ROKADE, P.B.; SONWANE, S.R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
Short term toxicity tests were made against fish Puntius ticto a freshwater teleost to dimethoate, in relation to study the effect of hardness of water on toxicity of dimethoate pesticide. The mortality rate were recorded under different hardness. The LC50 values of dimethoate for 24, 48, 72 and 96 hrs were obtained as 6.839, 5,555. 5.070. 5.012 ppm under normal conditions in laboratory. Hardness of water plays an important role in the toxicity of pesticide. The LC5o value at 100 ppm and 200 ppm hardness are 4.519 and 5.433, respectively. These values show that the dimethoate toxicity increases with decrease in hardness of water.